Effect of Ulva lactuca sap on the growth performance and mucosal immunity in Koi Carp (Cyprinus carpio koi) - S. Fathima Humtha; M. Navin Chandran (The Bioscan, 2025)
Cyprinus carpio koi is a beautiful ornamental fish known for its attractive patterns and colourations. Since it has a good demand for aesthetic purposes, its growth and the other factors are taken into consideration. In this study, algal sap of U. lactuca was used as a feed additive and coated along with commercial pellet diet of ornamental fish at various concentrations, i.e. 0.5%, 1.0% & 2.0% respectively. In parallel, a control diet lacking U. lactuca sap was maintained for analysis. Koi carp fed on U1, U2, & U3 diets showed a decline in weight gain, i.e. 0.86 ± 0.02g, 0.64 ± 0.03g & 0.57 ± 0.01g, whereas control diet fed fish showed an elevated weight gain of 1.02 ± 0.04g. Alternatively, the mucosal Immune parameters showed an enhanced trend in U1, U2, & U3 treated groups compared to the control diet-fed groups. Keywords Koi carp, Ulva lactuca sap, mucosal immunity